2021
DOI: 10.7717/peerj.11136
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis revealed gene regulatory network involved in PEG-induced drought stress in Tartary buckwheat (Fagopyrum Tararicum)

Abstract: Tartary buckwheat is a nutritious pseudo-cereal crop that is resistant to abiotic stresses, such as drought. However, the buckwheat’s mechanisms for responding to drought stress remains unknown. We investigated the changes in physiology and gene expression under drought stress, which was simulated by treatment with polyethylene glycol (PEG). Five physiological indexes, namely MDA content, H2O2 content, CAT activity, SOD activity, and POD activity, were measured over time after 20% PEG treatment. All indexes sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…In this study, we decided to use one C per inbred line because the drought resistance of the two inbred lines we used had already been established, and the main goal of our work was to identify the differentially expressed genes between the two lines and reveal the potential molecular mechanisms. Several researchers have already exploited this element of using a single control in drought and salinity stress studies in contrast to distinct time-point treatments [103][104][105].…”
Section: Plant Materials Growth Conditions and Drought Stress Treatmentsmentioning
confidence: 99%
“…In this study, we decided to use one C per inbred line because the drought resistance of the two inbred lines we used had already been established, and the main goal of our work was to identify the differentially expressed genes between the two lines and reveal the potential molecular mechanisms. Several researchers have already exploited this element of using a single control in drought and salinity stress studies in contrast to distinct time-point treatments [103][104][105].…”
Section: Plant Materials Growth Conditions and Drought Stress Treatmentsmentioning
confidence: 99%
“…Our previous comparison of the response of F. esculentum and F. tataricum to water stress showed that the former was more affected by water stress than the latter [ 45 ]. Fagopyrum tataricum was reported to be widely adaptable to hostile environments and resistant to abiotic stresses such as drought [ 41 , 43 , 62 ]. It is usually cultivated in the mountainous areas of western China, northern India, Bhutan, and Nepal at high altitude, and it regularly suffers from drought stress in its main growing regions [ 43 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Through whole-genome sequencing, Zhang et al [ 41 ] investigated genes related to abiotic stress resistance (including drought) in F. tataricum , and their data suggest that F. tataricum ’s ability to tolerate high levels of abiotic stress is attributed to the expansion of several gene families involved in signal transduction, gene regulation, and membrane transport. Huang et al [ 62 ] observed also a modification of several stress-response genes and genes coding for late embryogenesis abundant (LEA) proteins in response to drought stress in F. tataricum , and they showed that both the ABA-dependent and the ABA-independent pathway are involved in the regulation of drought stress in this species. Our results indicated that Zlata, PI481659, and PI481670 seemed less affected by water stress than the other varieties regarding flowering and yield parameters ( Table S2 ), although the best yield under 21 WS conditions was obtained for PI481671 and Lifago.…”
Section: Discussionmentioning
confidence: 99%
“…PEG6000 is mainly used to determine the drought stress-related information of plants ( Turkan et al, 2005 ). Studies have reported that PEG6000 is used to simulate drought in many medicinal plants, such as Astragalus membranaceus ( Liang et al, 2021 ), Sophora alopecuroides ( Yan et al, 2020 ), Fagopyrum tataricum ( Huang et al, 2021 ), Sophora moorcroftiana ( Li et al, 2015 ), etc. However, there are fewer reports on the mechanism of drought stress in Mesona Chinensis Benth.…”
Section: Introductionmentioning
confidence: 99%